PHENOMENOLOGICAL STUDY OF EXPORT SMEs FOREIGN PROMOTION PARTICIPANTS GAYENG UMKM PROGRAM - Mega Nazareth; I Made Sukresna (Jurnal Apresiasi Ekonomi, 2025)
This study aims to analyze the obstacles and challenges faced by MSMEs that are members of the Central Java Gayeng MSME program in exporting their products. The main focus of this study is to identify factors that inhibit exports and the strategies implemented to overcome them. The method used in this study is a qualitative approach with a case study, with data collection through in-depth interviews with informants who are MSME actors who have participated in the Gayeng MSME program and have export experience. The data analysis methods used include data reduction, categorization, and data display. Conclusions are drawn using a descriptive narrative approach.The results of the study indicate that the main obstacles in exporting Gayeng MSME products include internal constraints such as limited production and managerial capacity, as well as external constraints such as lack of infrastructure and complex regulations. In addition, this study also identifies various strategies implemented by MSMEs to facilitate exports, including increasing branding, production efficiency, and using consultant services. This study contributes to understanding the challenges of MSME exports in Central Java and provides policy recommendations to improve the export performance of the MSME sector in the future. Keywords: Obstacles, Challenges, Gayeng UMKM, Export, Policy